Association between living setting and malnutrition among older adults: The PEN-3S study - Madeira, T (2020)
Objectives Malnutrition is frequent among older adults, especially those living in nursing homes, but the association between residential setting and nutritional status is controversial. The aim of this study was to examine the association between living setting (nursing home versus community) and malnutrition while adjusting for demographic, socioeconomic, health-related, and psychosocial factors. Methods This cross-sectional study included a randomly selected representative sample of Portuguese adults ≥65 y of age. Interviewers collected data regarding demographic and socioeconomic characteristics, nutritional status, physical activity, energy intake, cognitive function, self-reported general health, functional status, symptoms of depression, and loneliness. Logistic regression models were used to estimate the association between residential setting and malnutrition. Results Participants were 1186 nursing home residents (72.8% women, 49.2% ≥85 y of age) and 1120 community dwellers (49% women, 21.3% ≥85 y of age). Following Mini Nutritional Assessment (MNA®) criteria, 29.6% of nursing home residents and 14.1% of community dwellers were at risk of malnutrition, whereas 2.3% and 0.3%, respectively, were malnourished. The living setting was not significantly associated with malnutrition after adjusting for functional status, symptoms of depression, and feelings of loneliness (odds ratio, 1.03; 95% confidence interval, 0.67–1.58). Conclusions Risk of malnutrition and malnutrition are more prevalent among nursing home residents than community dwellers. Physical (functional status) and mental health (symptoms of depression and loneliness) seems more relevant to nutritional status than residential setting by itself. These findings should be taken into account when designing public health policies to tackle malnutrition among older adults.